2013
DOI: 10.2147/amep.s46214
|View full text |Cite
|
Sign up to set email alerts
|

Effect of year of study on stress levels in male undergraduate dental students

Abstract: ObjectiveStress among dental students can be a significant threat, resulting in physical and/or mental illness, and have a negative effect on students’ performance and the professional practice of dentistry. Stress can occur from different sources. The purpose of this study is to test whether the year of study has an effect on the stress levels of dental students.MethodOur study consisted of a cross-sectional survey using a modified version of the Dental Environment Stress (DES) questionnaire. The questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
1
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 35 publications
2
49
1
9
Order By: Relevance
“…This is in line with others research that also used the DES questionnaire [2,6,8,19,24], but differs from other studies [7,12,25,26]. The perception of stress does not depend on the progress of the course, but would be influenced by gender and the first option of studying dentistry [12].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This is in line with others research that also used the DES questionnaire [2,6,8,19,24], but differs from other studies [7,12,25,26]. The perception of stress does not depend on the progress of the course, but would be influenced by gender and the first option of studying dentistry [12].…”
Section: Discussionsupporting
confidence: 87%
“…The perception of stress does not depend on the progress of the course, but would be influenced by gender and the first option of studying dentistry [12]. Third-year students had the highest levels of perceived stress, which they attribute to the transition phase from pre-clinical to clinical, where they begin to relate with patients and meet requirements [7,25]. On the other hand, some authors reported that the first two years of the career, students have greater perception of stress [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of these investigations have shown that psychological stress was highest in final year students and lowest in first year students [2, 9, 11]. Some studies however have found that stress was highest in third year students when the transition to clinical teaching occurred [3, 10]. This would seem to imply that as students progressed through dental school, their level of stress increased, but due to the cross-sectional nature of these investigations, this assumption could not be verified.…”
Section: Introductionmentioning
confidence: 99%
“…Factorial analysis allows identification of how the items are organized in subscales according to the samples' constructs instead of being theoretically divided. The stressful potential of the subscale Academic Performance is well documented, with the item "Examinations and Grades" being frequently perceived as the most stressful [38][39][40] . An inverse relationship was detected between this subscale and SIgA concentration and secretion rate among 2nd year students, which corroborates previous findings…”
Section: Discussionmentioning
confidence: 99%